2015
DOI: 10.1080/09593330.2015.1049216
|View full text |Cite
|
Sign up to set email alerts
|

Application of simple and low-cost toxicity tests for ecotoxicological assessment of industrial wastewaters

Abstract: The objective of this study was to identify and to apply appropriate biotests having the advantages of being highly sensitive, easy to run, relatively inexpensive and able to substitute fish toxicity tests due to ethical reasons of animal welfare. To perform an ecotoxicological assessment of industrial wastewaters, different microbiotests were conducted to substitute the fish toxicity test with Lebistes reticulatus through Vibrio fischeri, Thamnocephalus platyurus, Daphnia magna, Lemna minor and Lepidium sativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Interestingly, it was found that the aquatic organisms used for the investigation of PS MNP toxicity were more likely to be invertebrates than fishes (32 vs. 24 studies). This is probably due to the high sensitivity, inexpensive management, and ease of running experimental tests with invertebrates compared to vertebrates, besides the ethical rationale for animal welfare [47]. Moreover, transcriptomics and metabolomics appeared to be the approaches used mostly for fishes (a total of 11 out of 24 studies used transcriptomics and a total of 11 out of 24 studies used metabolomics in fish), while in the case of aquatic invertebrates, the most common -omic approach used was found to be the transcriptomics (a total of 18 out of 32 studies).…”
Section: -Omics Approaches In Studies Of Ps Mnp Toxicitymentioning
confidence: 99%
“…Interestingly, it was found that the aquatic organisms used for the investigation of PS MNP toxicity were more likely to be invertebrates than fishes (32 vs. 24 studies). This is probably due to the high sensitivity, inexpensive management, and ease of running experimental tests with invertebrates compared to vertebrates, besides the ethical rationale for animal welfare [47]. Moreover, transcriptomics and metabolomics appeared to be the approaches used mostly for fishes (a total of 11 out of 24 studies used transcriptomics and a total of 11 out of 24 studies used metabolomics in fish), while in the case of aquatic invertebrates, the most common -omic approach used was found to be the transcriptomics (a total of 18 out of 32 studies).…”
Section: -Omics Approaches In Studies Of Ps Mnp Toxicitymentioning
confidence: 99%
“…Os ensaios ecotoxicológicos são importantes parâmetros para avaliação da toxicidade de efluentes bruto e pós-tratado. Esses bioensaios fazem uma avalição do impacto de efluentes em espécies vivas e avaliam o desempenho dos processos de tratamento de águas residuárias visto que, as análises químicas não detectam as interações sinérgicas, antagônicas ou aditivas entre os contaminantes (Aydin et al, 2015;Methneni et al, 2021).…”
Section: Coagulação Fenton: Impactos Ao Ambiente E Seu Monitoramentounclassified
“…Muitos organismos de solo e aquáticos são bioindicadores sensíveis de contaminação. Os testes de toxicidade podem ser realizados com organismos tanto de solo quanto aquáticos com objetivo de detectar e prever os efeitos nocivos dos produtos químicos na população, nas comunidades e nos ecossistemas (Aydin et al, 2015).…”
Section: Coagulação Fenton: Impactos Ao Ambiente E Seu Monitoramentounclassified
“…Wastewater is generated through various sources such as homes, industries, farms, and various other ways. As a result, the complexity of wastewaters comprising of both natural and synthetic organic substances and high volumes of industrial chemicals are possible contaminants that cause toxic effects in wastewater [3]. These constitute potential dangers to the natural water system and hence becomes hazardous to life and the environment [30].…”
Section: Article Highlightsmentioning
confidence: 99%